Analisis Pengaruh Parameter Pemesinan CNC Milling terhadap Material Removal Rate pada Dudukan Cetakan Kampas Rem - Hadi Usman; Eko Yudo; Sukanto Sukanto (Jurnal Inovasi Teknologi Terapan, 2026)
This study investigates the influence of CNC Milling parameter variations on the Material Removal Rate (MRR) of S45C steel brake lining mold holders using the Taguchi method. Three parameters—spindle speed, feed rate, and depth of cut—were tested at three levels through an L9 experimental design. Data were analyzed using the signal-to-noise ratio, ANOVA, and normality testing. Results indicate that none of the parameters significantly affect MRR at the 5% level (Fcount < Ftable = 19.00). Depth of cut showed the highest relative contribution (7.39%), while spindle speed and feed rate contributed negatively. A high error value (92.99%) suggests unobserved external factors. The optimal combination is 2388 rpm, 191 mm/min, and 2.67 mm, yielding a predicted MRR of 90.0766 (CI ±0.4126). Normality assumptions were met (p > 0.150).